1995
DOI: 10.1073/pnas.92.22.10177
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gene encoding the alpha subunit of the rod cGMP-gated channel in autosomal recessive retinitis pigmentosa.

Abstract: Mutations in the genes encoding two proteins of the retinal rod phototransduction cascade, opsin and the j3 subunit of rod cGMP phosphodiesterase, cause retinitis pigmentosa (RP) in some families. Here we report defects in a third member of this biochemical pathway in still other patients with this disease. We screened 94 unrelated patients with autosomal dominant RP and 173 unrelated patients with autosomal recessive RP for mutations in the gene encoding the a subunit of the rod cGMP-gated cation channel. Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
195
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(197 citation statements)
references
References 19 publications
2
195
0
Order By: Relevance
“…In a similar fashion, rods degenerate in animals (including humans) that lack functional cGMP-gated channels. (64,65) The knocking out of the channels should also cause a maintained lowering of the Ca 2þ concentration, since the entry pathway for Ca 2þ into the outer segment is eliminated, but there is one difficulty with this notion. The channel in the outer segment is tightly associated with the Na þ /Ca 2þ -K þ exchange protein, (66,67) with two exchanger molecules bound to each channel heteromer.…”
Section: Why Does Continuous Activation Kill?mentioning
confidence: 99%
“…In a similar fashion, rods degenerate in animals (including humans) that lack functional cGMP-gated channels. (64,65) The knocking out of the channels should also cause a maintained lowering of the Ca 2þ concentration, since the entry pathway for Ca 2þ into the outer segment is eliminated, but there is one difficulty with this notion. The channel in the outer segment is tightly associated with the Na þ /Ca 2þ -K þ exchange protein, (66,67) with two exchanger molecules bound to each channel heteromer.…”
Section: Why Does Continuous Activation Kill?mentioning
confidence: 99%
“…The chromosomal localization will be useful in the search of candidate genes for retinal disorders. Mutations in the rod channel c~-subunit have been linked to certain cases of autosomal recessive retinitis pigmentosa, characterized by a degeneration of the rod photoreceptors [36]. It may be clinically relevant to know whether mutations in the cone channel gene can lead to cone-specific diseases.…”
Section: Vk Yu Et Al/febs Letters 393 (1996) 211~15mentioning
confidence: 99%
“…The knowledge of the sequence and gene location will provide a useful basis for examining human diseases involving this channel gene. In the retina, mutations in the rod CNG channel have been shown to lead to certain cases of autosomal recessive retinitis pigmentosa [36]. At the same time, we were curious to know whether the human cone channel (c~-subunit) is sensitive to Ca2+-calmodulin as reported for the bovine homolog.…”
Section: Introductionmentioning
confidence: 99%
“…9 It is of interest to note that some recessively inherited forms of retinitis pigmentosa, a common degenerative retinal disease, are caused by mutations in PDE-6. 12 In mice heterozygous for a mutation causing absence of the g-subunit of PDE-6, it was found that reversible dose-dependent ERG changes occurred following treatment with sildenafil. 13 Although further study is required, these findings imply that PDE-5 inhibitors could have a significant impact on retinal function in patients with retinitis pigmentosa and even in carriers of PDE-6 mutations.…”
Section: Transient Visual Side Effects Of Pde-5 Inhibitorsmentioning
confidence: 99%